Hepatoprotective effect of Bauhinia purpurea L. methanolic leaves extract - Yahya, Farhana (2014)
The objective of this study was to determine the hepatoprotective activity of methanolic extract of Bauhinia purpurea (Fabaceae) leaves (MEBP) and its partitions using rat models, i.e., by evaluating the prophylactic effect of the plant extracts administered prior to the induction of liver toxicity using a hepatotoxic agent. The study was designed as a preventive method, as the hepatoprotective potential of MEBP has never been reported. In an attempt to establish the pharmacological properties of B. purpurea, the hepatoprotective potential of MEBP was investigated using paracetamol (PCM)- and carbon tetrachloride (CCl4)-induced hepatotoxicity in rats. Throughout this study, the animals were divided into 22 groups containing 6 rats per group. For the first stage of the in vivo study, rats were divided into groups and administered orally once daily with 10% dimethyl sulfoxide (DMSO) (negative control), 200 mg/kg silymarin (positive control), or MEBP (50, 250, 500 mg/kg) for 7 days, followed by hepatotoxicity induction using PCM or CCl4. In the second stage of the in vivo study, MEBP was partitioned into 3 fractions: petroleum ether extract (PEBP), ethyl acetate extract (EABP), and aqueous extract (AQBP). PEBP, EABP, and AQBP activities were tested on PCM-induced hepatotoxicity in rats. Blood samples underwent biochemical analysis to evaluate alanine transaminase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), and total protein (TP) levels; the livers were subjected to microscopic analysis. All extracts (MEBP, PEBP, EABP, AQBP) underwent antioxidant study using the 2, 2-diphenyl-1-picrylhydrazyl radical scavenging assay (DPPH), superoxide dismutase scavenging assay (SOD), and oxygen radical absorbance capacity assay (ORAC), and anti-inflammatory study using lipoxygenase (LOX) and xanthine oxidase (XO) assays. Total phenolic content (TPC), phytochemical screening, and high-performance liquid chromatography (HPLC) analysis were also performed. From the histological observation, lymphocyte infiltration and marked necrosis were observed in the DMSO-treated groups (negative control). MEBP showed encouraging activity for reducing the toxic effect of CCl4 and PCM on the liver by reducing the weight of the liver in a dosedependent manner; histological observation demonstrated normalization of the histopathological changes, preserving hepatocyte structure, causing a significant decline in ALT and AST levels (p < 0.05) and escalation of TP level. PEBP, which contains non-polar compounds, reduced the liver enzyme levels in a dose-dependent manner and increased the production of TP. EABP and AQBP, which contain intermediate compounds and polar compounds, respectively, attenuated the liver enzyme and LDH levels (concentration-independent). Among the extracts, EABP had the best activity for attenuating the liver enzymes. MEBP had the highest TPC value, followed by EABP, AQBP, and PEBP. EABP and MEBP demonstrated potential free radical scavenging activity in the SOD assay. The trend for the ORAC assay was slightly different from that of the DPPH and SOD assays. AQBP and EABP had high ORAC value, which determines the capacity of an extract to act as an antioxidant. All extracts in the present study had weak anti-inflammatory activity in the inhibition of LOX and XO. Phytochemical screening of the extracts showed that MEBP, PEBP, and EABP contained flavonoids, tannins, polyphenolic compounds, and steroids. However, the phytochemical screening showed that AQBP contained fewer compounds. HPLC analysis demonstrated several peaks detected at different wavelengths of the chromatogram of MEBP, EABP and AQBP, which were suggested to be flavonoid-based compounds. In conclusion, MEBP exerted potential hepatoprotective activity that can be partly attributed to its antioxidant activity, and EABP was considered to have the best activity among the fractions, which warrants further investigation.